Distribution of light alkanes in the reaction of graphite hydrogenation at pressure of 0.1–7.8 GPa and temperatures of 1000–1350°C. Issue 4 (2nd October 2018) - Sokol, Alexander G.; Tomilenko, Anatoly A.; Bul'bak, Taras A.; Sokol, Ivan A.; Persikov, Eduard S.; Bukhtiyarov, Pavel G.; Palyanov, Yury N.
ABSTRACT: We studied the effect of pressure and temperature on the hydrocarbon (HC) chain length distribution and total amount of HCs in the reaction of direct graphite hydrogenation at pressures of 0.1–7.8 GPa and temperatures of 1000–1350°C. An increase in pressure was found to lead both to an increase in the absolute yield of HCs due to direct graphite hydrogenation and to chain elongation of HC products. Light alkanes predominate among HCs in the entire studied range of P–T parameters. However, their concentration in quenched fluids increases as pressure is elevated, from less than 10 rel.% at 0.1 GPa to more than 40–50 rel.% at P ≥ 3.8 GPa. Methane is actually the only light alkane among reaction products at 0.1 GPa and 1000°C, while it is a minor component at 7.8 GPa and 1350°C. The most stable alkane at pressures above 3.8 GPa is ethane (C2 H6 ).